On the toxicity of cellulose nanocrystals and nanofibrils in animal and cellular models - Ventura, Célia (2020)
The need for reaching environmental sustainability encourages research on new cellulose-based materials for a broad range of applications across many sectors of industry. Cellulosic nanomaterials obtained from different sources and with different functionalization are being developed with the purpose of its use in many applications, in pure and composite forms, from consumer products to pharmaceutics and healthcare products. Based on previous knowledge about the possible adverse health effects of other nanomaterials with high aspect ratio and biopersistency in body fluids, e.g., carbon nanotubes, it is expected that the nanometric size of nanocellulose will increase its toxicity as compared to that of bulk cellulose. Several toxicological studies have been performed, in vitro or in vivo, with the aim of predicting the health effects caused by exposure to nanocellulose. Ultimately, their goal is to reduce the risk to humans associated with unintentional environmental or occupational exposure, and the design of safe nanocellulose materials to be used, e.g., as carriers for drug delivery or other biomedical applications, as in wound dressing materials. This review intends to identify the toxicological effects that are elicited by nanocelluloses produced through a top-down approach from vegetal biomass, namely, cellulose nanocrystals and nanofibrils, and relate them with the physicochemical characteristics of nanocellulose. For this purpose, the article provides: (i) a brief review of the types and applications of cellulose nanomaterials; (ii) a comprehensive review of the literature reporting their biological impact, alongside to their specific physicochemical characteristics, in order to draw conclusions about their effects on human health.